ÙØ¹Ø§Ù„ÙŠØ© ØªØ¹Ù„ÙŠÙ… Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙƒØªØ§Ø¨ Ù…ØªÙ† Ø§Ù„Ø£Ø¬Ø±ÙˆÙ…ÙŠØ© Ù„ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© - islahul ummah; idiatussaufiah idiatussaufiah (Lughatu Ad-dhat, 2021)
Based on the problem of reduced reading ability of the pupils, the researcher was interested in conducting the search for grammar. As for the research method, which uses quantitative and experimental methods. The research design used is a quasi-experimental design. This study aims to find out, is there an effective teaching of the rules using the text book al-Ajrami to upgrade the reading skill for the eleventh semester of the high school teachers Nahdhat Al-Watan Publishing. The results of the study show that there is a difference of importance, for the ability of reading skill, separation of experimentation and separation of control, and this is evidenced by obtaining the average value of the experimental class, an increase of 74.34 from the first degree of 1531, which increased to 2602. While for the control class, an increase of an average value of 61.97. From the initial result of 1415, it increased to 2169.By looking at the different results of each chapter, it appears that the text of Al-Jarouniyah is an effective medium for learning to read.